Geographical information system counter position at PT. Web-based Millennium Plaza - Sri Hartati (Cebong Journal, 2022)
The development of computer technology has a positive impact on all life, especially in the world of industry, education, government and small to medium businesses. Where with the existence of computer technology all work done manually can be done computerized. A well-designed information system will greatly assist organizations or companies in obtaining accurate, timely and relevant information in their presentation. PT. Millennium Plaza is one of the many companies engaged in counter rental services in the city of Medan. In this case the author designed an information system that supports company performance, namely "Geographical Information System Counter Position at PT. Web-based Millennium Plaza” which was developed using PHP and using the MySQL database processing application. This program allows users to be able to work more effectively and efficiently in terms of entering data, deleting data, changing data to printing data. And all the data has been stored in the database so it's easy to process it. The end result of designing a geographic information system for counter positions is expected to help search and present data more effectively and accurately.